Housing Activism and Urban Space during the Covid19 Pandemic. Research Notes on the Bairro of Arroios, Lisbon - Allegra, Marco; Carbone, Claudio (PARTECIPAZIONE E CONFLITTO, 2023)
This paper presents some research notes from an on-going project on housing activism in Lisbon in the last decade, describing its ascendant trajectory (2012-2019) and the impact that the Covid epidemic had on the local activist community (2020-2022). In particular, the paper focuses on two of the main protagonists of local housing activism, the association Habita and the collective Stop Despejos, and on the relation that they have developed in time with an ecosystem (of sites, groups, projects) that have developed in the last ten years in the neighbourhood of Arroios, which have found a characteristic spatial infrastructure in the coletividades (a Portuguese expression that identifies spaces managed by no-profit associations or collectives). The paper examines this relation against the background of two bodies of literature, namely contributions that have examined (i) the nexus between collective action and space and (ii) the different forms of political agency represented by the conceptual pole of "contentious" and "everyday politics". This research is based on extensive data collection (through ethnographic notes, documental analysis, and in-depth interviews, 2020-2022) and on the authors' status of insiders in the process observed.